Three-dimensional scanning for breast plastic and reconstructive surgery: An updated review - Jin, Ming-Yuan; Lin, Xiao-Ying; Wang, Yong; Zhuang, Ze-Ming; Zhong, Xin-Cao; Zhang, Tao; Li, Ying; Tan, Wei-Qiang (European journal of plastic surgery, 2024)
Breast plastic and reconstructive surgery are widely performed worldwide. There are various tools available to improve surgical outcomes. Among them, three-dimensional (3D) scanning is of considerable value. 3D scanning consists of hardware and software with multiple working principles. This review summarizes the recent advances in the application of 3D scanning in breast plastic and reconstructive surgery, including measuring aesthetic parameters, formulating preoperative plans, and evaluating postoperative results. The development trend of 3D scanning is to integrate with portable devices, 3D printing, deep learning, and telemedicine, opening up a wide and abundant range of application scenarios. In brief, 3D scanning plays a vital role in breast plastic and reconstructive surgery. As an auxiliary tool, it improves preoperative and postoperative satisfaction for both surgeons and patients. With the new round of medical revolution, the further development of 3D scanning will open up an efficient, digital, and intelligent field for breast plastic and reconstructive surgery. Level of evidence: Not ratable.